2017
DOI: 10.1144/sp468.4
|View full text |Cite
|
Sign up to set email alerts
|

The isotopic structures of geological organic compounds

Abstract: Organic compounds are ubiquitous in the Earth's surface, sediments and many rocks, and preserve records of geological, geochemical and biological history; they are also critical natural resources and major environmental pollutants. The naturally occurring stable isotopes of volatile elements (D, 13C, 15N, 17,18O, 33,34,36S) provide one way of studying the origin, evolution and migration of geological organic compounds. The study of bulk stable isotope compositions (i.e. averaged across all possible molecular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 95 publications
1
33
0
Order By: Relevance
“…Similarly, three independent techniques have been developed to measure the 13 C positionspecific signatures of propane (Gao et al 2016;Gilbert et al 2016, Piasecki et al 2016. Eiler et al (2017), in this volume, review published and unpublished work on the isotopic anatomy of organic molecules larger than methane, and outline potential future constraints offered by clumped isotope and site-specific analysis of organic molecules (e.g. biosynthesis, maturation, and the environmental conditions of hydrocarbon generation and storage).…”
Section: The New Frontier In Geochemical Applications In Petroleum Symentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, three independent techniques have been developed to measure the 13 C positionspecific signatures of propane (Gao et al 2016;Gilbert et al 2016, Piasecki et al 2016. Eiler et al (2017), in this volume, review published and unpublished work on the isotopic anatomy of organic molecules larger than methane, and outline potential future constraints offered by clumped isotope and site-specific analysis of organic molecules (e.g. biosynthesis, maturation, and the environmental conditions of hydrocarbon generation and storage).…”
Section: The New Frontier In Geochemical Applications In Petroleum Symentioning
confidence: 99%
“…Gilfillan et al 2009). Finally, the isotopic approaches described in Eiler et al (2017), Gao et al (2017), Pedentchouk & Turich (2017) and Stolper et al (2017) all have the capability to elucidate the origin of hydrocarbons in the environment.…”
mentioning
confidence: 99%
“…Notably, when a isotope exchange reaction is in equilibrium, the Δ value reflects temperature and thus is used as a geothermometer. 2,3 This approach was originally developed from the study of 13 C- 18 O clumped species in CO 2 and carbonates, 4,5 and was then applied to 18 O- 18 O clumped species in O 2 , 13 C-2 H in CH 4 , 15 N-18 O in N 2 O, 13 C-13 C in C 2 H 6 and 15 N-15 N in N 2 . [6][7][8][9][10] The analysis of clumped species in CH 4 , N 2 O, C 2 H 6 and N 2 has been made possible thanks to the development of high-resolution mass spectrometry (HRMS) and laser spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…8,12 Despite the potential of the clumped isotope analysis, the measurement is still limited to a few molecules. 2,[4][5][6][7][8][9][10][11][12] Notably, 13 C- 13 C bonding exists in a wide range of organic compounds, although it has seldom been studied owing to the technical difficulty. Clog et al 9 first reported the measurement of the 13 C-13 C isotopologue of the C 2 compound ethane by using HRMS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation